Macaronesian Muscidae (Diptera). I. The genus Hebecnema Schnabl with description of a new Canarian endemic species and a review of the European fauna - Michelsen, Verner (Zootaxa, 2019)
An account is given on the three species of the muscid genus Hebecnema Schnabl occurring in the Macaronesian islands. These are Hebecnema anthracina Stein from Madeira, H. anthracinella sp. nov. from the western Canary Islands, and H. fumosa (Meigen) found in the Canary Islands, Madeira and Azores. Existing Macaronesian records of H. umbratica (Meigen) from the Azores and H. vespertina (Fallén) from the Canary Islands are based on misidentifications. Diagnoses of the European species with photos of the male terminalia and a key to species are given. It is pointed out that the two species of Muscidae recently described as new from Sweden, Mydaea forsslundi Zielke, 2017 and Hebecnema brodina Zielke, 2018, represent exotic species, probably of Oriental provenance. Finally, morphological differences in the female ovipositor divide the seven European species of Hebecnema in two species groups.